Safety and toxicity risks of radiotherapy combined with PD-1/PD-L1 inhibitors: A comprehensive review - Lijing Zeng; Jing Yang; Huang Xia; Zeyuan Li; Yu Lin; Qiwei Yao; Rong Zheng (iScience)
Summary: Radiotherapy (RT) combined with PD-1/PD-L1 Inhibitors has demonstrated remarkable efficacy across various cancers. However, concerns remain regarding its safety and potential toxicity. We analyze toxicity risks of RT combined with anti–PD-1/PD-L1 therapy based on current clinical studies. While a slight increase in grade 1–2 pneumonitis has been reported in patients with lung cancer, no consistent evidence suggests a rise in ≥ grade 3 pulmonary toxicity. Additionally, the combination appears well tolerated in the central nervous system, head and neck, and hepatic malignancies. This narrative review investigates key factors that may influence the risk of toxicity in combination therapy, including the dose and fractionation of RT, sequencing with immunotherapy, timing and duration of immune consolidation, and regimen heterogeneity. This review adheres to the SANRA (Scale for the Assessment of Narrative Review Articles) guidelines.